Developmentally controlled subcellular remodeling and VND-initiated vacuole-executed PCD module shape xylem-like cells in peat moss - Ningjing Liu; Qiuqi Guo; Fangming Shi; Lei Gao; Yongqi Liu; Yiwen Wang; Zhiwei Gong; Haoran Liu; Yue Sun; Bosheng Li; Bing Ni; Rui-Liang Zhu; et al. (Communications Biology)
Abstract Peat moss (Sphagnum) is a non-vascular higher plant with unique xylem-like hyaline (H) cells that are accompanied by photosynthetic chlorophyllous cells. These cellular structures play crucial roles in water storage and carbon sequestration. However, it is largely unknown how peat moss develops the H cells. This study systematically explored the Sphagnum Developmental Cell Atlas and Lineage and classified leaf cell development into two lineages with six stages (S0-S5) based on changes in key cellular traits, including the formation of spiral secondary cell walls (S4) and the presence of water pores (S5). Cell lineage-specific subcellular remodeling was transcriptionally regulated during leaf development, and vacuole-mediated clearance of organelles and cell death led to mature dead H cells. Interestingly, expression of land plant conserved Vascular-related NAC Domain (VND) genes correlated with H cell formation. Overall, these results suggest that the origination of xylem-like H cells is related to VND, likely through the neofunctionalization of vacuole-mediated cell death to attempt xylem formation in peat moss, suggesting potential uncoupling of xylem and phloem cell origins. This study positions peat moss as a potential model organism for studying integrative evolutionary cell biology.